Percutaneous Cannulated Screw Fixation vs. Plating With Minimally Invasive Longitudinal Approach After Closed Reduction for Intra-Articular Tongue-Type Calcaneal Fractures: A Retrospective Cohort Study - Cao, Yuan; Xu, Xiangyu; Guo, Yan; Cui, Zengzhen; Zhao, Yang; Gao, Shan; Tian, Yun; Lv, Yang; Zhou, Fang (Frontiers in Surgery, 2022)
Objective: Displaced intra-articular tongue-type fractures are often treated with surgical interventions, and there is a lack of consensus regarding the surgical approach. This retrospective cohort study aimed to compare percutaneous cannulated screw (PCS) fixation and plating with a minimally invasive longitudinal approach (MILA) after closed reduction for the treatment of tongue-type calcaneal fractures. Materials and methods: A total of 77 patients with intra-articular tongue-type calcaneal fractures between September 2015 and July 2019 were included in this study. They were randomly allocated into two groups: PCS fixation (n = 32) and MILA (n = 45). The outcome measures included demographic variables, operation time (OT), preoperative time (POT), hospital stay time (HST), blood loss, visual analog scale (VAS) scores, American Orthopaedic Foot and Ankle Society (AOFAS) hindfoot scores, postoperative complications, and imaging parameters. The patients were clinically examined at 1, 3, 6, and 12 months, with a final follow-up period of 27 months. Results: No significant differences were observed during the follow-up in calcaneal length, height, Gissane’s and Böhler’s angles, VAS scores, AOFAS hindfoot scores, or complication rates between the two groups. However, the postoperative VAS scores in the PCS group were significantly lower than those in the MILA group (p < 0.05). Furthermore, the OT, POT, and HST in the PCS group were significantly shorter than those in the MILA group (p < 0.05). Blood loss was lower in the PCS group than those in the other groups (p = 0.044). However, postoperative calcaneal widening was significantly smaller in the MILA group than that in the PCS group (p < 0.001). Conclusions: After closed reduction for the treatment of tongue-type calcaneal fractures, PCS fixation was superior to MILA in terms of OT, POT, HST, blood loss, pain, and degree of comfort. Meanwhile, MILA has the advantage of restoring the calcaneal width. Under the same rehabilitation program, the two approaches showed similar abilities in maintaining the closed reduction.